The adoption of social media by Thai university students: Multiple group moderating effects - Suksa-ngiam, Watanyoo; Chaiyasoonthorn, Wornchanok (My University, 2015)
The purposes of this research are to explain why Thai university students use social media and how differences between groups of respondents moderate the structure of relationships. Four core latent constructs were investigated in this study: behavioural intention (BI), subjective norms (SN), perceived ease of use (PEOU), and perceived usefulness (PU). Two moderating variables, gender and age, were employed to answer the research questions. Respondents (n = 600) in three universities in Bangkok, Thailand, were selected and Structural Equation Modelling (SEM) was employed to analyse the data. The results show that behavioural intention is influenced by perceived ease of use, subjective norm, and perceived usefulness respectively. Perceived usefulness is also influenced by perceived ease of use. Moreover, our study affirms that the path from subjective norm to behavioural intention is moderated by age. This path is stronger for older people than for younger people. Discussions, limitations, and recommendations for future research are addressed.
Keywords: social media; Thailand; university students; user studies